A etnobotânica e os saberes regionais : aliando o saber popular ao potencial biotecnológico de plantas na Comunidade de Aldeia Velha, Chapada dos Guimarães, Mato Grosso, Brasil - Silva, Larissa Cavalheiro da (2018)
Relations established between peoples and nature are fundamental to understand this dynamic. Studies focused on ethno-cognition and ethnobotany can define strategies aimed at the conservation of biodiversity and the preservation of cultural heritage. The study area is located in Chapada dos Guimarães / MT delimited by the geographical coordinates 15º30 '- 15º40' S and 55º35 '- 55º50' W. The target community was that of Aldeia Velha, a name also given to the first and oldest neighborhood of the County. Interviews were conducted through semi-structured questionnaires to delineate the profile of the group whose sampling technique was the so-called "snowball". The interviewees were mostly married women, ranging in age from 33 to 81 years, with incomplete elementary schooling. The community is mainly made up of people who have been living there for a long time (more than 20 years). This study cataloged 72 species belonging to 39 families. The families with the highest number of species were Asteraceae (nine species), Lamiaceae (seven species), Fabaceae (four species) and Poaceae, Rutaceae, Solanaceae and Zingiberaceae (three species each). Of the parts of the plant used by the community, the leaves were the most used with 75% of citations by the informants; among the forms of preparation of these plants, 70% of the informants commonly use tea (infusion). Within the sampled universe, more than 80% is considered medicinal and 20% is food or used for crafts and rituals. Within the plants considered medicinal, the great part of them is used for inflammation, disorders of the respiratory system, disorders of the digestive and metabolic system and disorders of the genitourinary system. Finally, we indicate seven species occurring in the cerrado of Chapada with biotechnological potential: Amburana cearensis (Allemão) A.C.Sm. (Fabaceae), Mikania glomerata Spreng (Asteraceae), Pseudobrickellia brasiliensis (Spreng.) R.M.King & H.Rob. (Asteraceae), Equisetum giganteum L. (Equisetaceae), Polygonum punctatum Elliott (Polygonaceae), Lafoensia pacari A.St.-Hil. (Lythraceae) and Momordica charantia L. (Cucurbitaceae), with particular emphasis on the first three in which conservation measures are necessary due to their high risk of extinction and / or vulnerability.